¿Podía hacer saber Unamuno a Augusto Pérez que es un personaje ficticio?: Una contribución a la epistemología del pensamiento dialógico - Ariso, José María (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2011)
This work describes a series of epistemological limitations intrinsic to the relationship between the novelist and his/her fictitious characters. In order to illustrate these limitations as clearly as possible, the dialogue held by Unamuno and his fictitious character Augusto Pérez in Niebla is analyzed